PENGARUH PENDEKATAN APOS (ACTION, PROCESS, OBJECT, SCHEMA) TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK PADA KELAS XI IPA SMA ADABIAH PADANG - Mardiana - (Jurnal Edukasi dan Penelitian Matematika, 2019)
Understanding of mathematics concepts is the basic ability that must be possessed by students. But in reality, students’ understanding of mathematics concepts in grade XI IPA SMA Adabiah Padang were still weak and learning process was still centered on educators. The solution that could be applied was APOS approach which made students construct concepts well. The purpose of the study was to describe whether the application of APOS can improve students’ understanding of mathematics conceptsand how the development of students’ understanding of mathematics conceptsafter APOS approach is applied. The type of research was pre experiment One Group Pretest-Posttest Design. The research hypothesis was proven by t-test. From the data analysis, for the level of   understanding of mathematics concepts of students after being treated with APOS approach is better than understanding the mathematics concepts of students before being treated with the APOS approach and development of students’ understanding of mathematics conceptsfluctuated at each meeting.Keywords - APOS (Action, Process, Object, Schema), understanding of mathematics concepts